PSYCHOSOSIAL FACTORS ON THE PERFORMANCE OF HEALTH OFFICERS - Dewi Ayu; M Fais Satrianegara; Fatmawaty Mallapiang (Homes Journal = Hospital Management Studies Journal, 2021)
Background:Psychosocial factors have become a major concern in occupational health. Changes that occur in the labor market, namely increased globalization, competition, flexibility, and new forms of work organization. Objective:The purpose of this study was to describe the psychosocial factors on the performance of health workers in Puskesmas X Makassar City.Method:This research method is a descriptive quantitative research with a population of all health workers at Puskesmas X Makassar City as many as 55 people using total sampling. The collected data were then analyzed by univariate and bivariate. Result:The results of data analysis showed that the majority of health workers at Puskesmas X Makassar City experienced severe stress as much as 50.9%, heavy loads as much as 65.5%, and mild fatigue as much as 67.3% with optimal good quality performance. This illustrates that health workers experience psychosocial factors that have a positive impact on performance, and to produce good performance.Conclusion:It is necessary to create a psychosocial environment so that individuals feel comfortable in groups and organizations, showing high productivity and improving the quality of work.